2016
DOI: 10.2147/ndt.s97724
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting treatment adherence to atomoxetine in ADHD: a systematic review

Abstract: The purpose of this paper was to systematically review the literature related to research about the factors affecting treatment adherence and discontinuation of atomoxetine in pediatric, adolescent, and adult patients with attention-deficit/hyperactivity disorder (ADHD). Medline was systematically searched using the following prespecified terms: “ADHD”, “Adherence”, “Compliance”, “Discontinuation”, and “Atomoxetine”. We identified 31 articles that met all inclusion and exclusion criteria. The findings from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Moreover, in most studies, adherence was limited to compliance with and discontinuation of treatment in controlled settings. The inclusion of real-world observational trials may provide a better understanding of treatment adherence in naturalistic settings (Treuer, Me´ndez, Montgomery, & Wu, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, in most studies, adherence was limited to compliance with and discontinuation of treatment in controlled settings. The inclusion of real-world observational trials may provide a better understanding of treatment adherence in naturalistic settings (Treuer, Me´ndez, Montgomery, & Wu, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…Clinical guidelines suggest that drug treatment is the preferred treatment for school-aged children with ADHD (10), and the side effects of most drugs are mild and gradually tolerated. However, parents, especially the parents of the younger age group, are still worried about the potential side effects, causing a low acceptance of and adherence to pharmacological intervention (47). Further, given that some parents might not be able to take part in field parent training due to varieties of reasons while children participated in GEF training, we launched the OPT course.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study showed that 47% of patients responded well to atomoxetine, 13% had a minimal response, and 40% did not respond (Newcorn, Sutton, Weiss & Sumner, 2009). Furthermore, discontinuation of atomoxetine ranged from 8.4% to 26% due to the lack of efficacy (Sugimoto et al, 2021;Treuer, Méndez, Montgomery & Wu, 2016). Marked differences in atomoxetine concentrations may explain some of the variability in its clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%